THE EFFECTIVENESS OF ANDROID-BASED INTERACTIVE MULTIMEDIA IN IMPROVING JUNIOR HIGH SCHOOL STUDENTS ENGLISH LEARNING OUTCOMES AND LEARNING MOTIVATION - Nurlaela, Dewi; Santhi, Dessy Dwi Yudha; Ardiasih, Lidwina Sri (Premise: Journal of English Education and Applied Linguistics, 2024)
Android-based interactive multimedia based on articulate storylines three is starting to be used to improve student learning outcomes and learning motivation. This study examines how interactive media is used in English lessons for junior high school students. This study aims to determine a) whether Android-based interactive multimedia effectively improves students' English learning outcomes, b) explain how Android-based interactive multimedia can increase students' Motivation in their English learning, and c) how students perceive implementing Android-based interactive multimedia in English learning. This study employs experimental research methods. A quasi-experimental design shows how Android-based interactive multimedia for English subjects can improve student learning outcomes and Motivation. The researcher used documentation, tests, and questionnaires as instruments research gathered to measure the aims of the study. As it was a quasi-experiment, the sample used was 66 students, including 33 students in the control class and 33 students in the experimental class. The findings revealed that a) using Android-based interactive multimedia effectively improves students' English learning outcomes, b) Android-based interactive multimedia increases students' Motivation for English learning, and c) Android-based interactive multimedia is appropriate for learning English.In conclusion, implementing Android-based interactive multimedia is worth doing in English learning, especially in junior high school. From these findings, choosing the suitable learning media can influence student learning achievement. Likewise, students' Motivation to learn influences their outcomes in English. Students with high learning motivation certainly have better learning achievements than students with average or low learning motivation.